2002
DOI: 10.1067/mcp.2002.126706
|View full text |Cite
|
Sign up to set email alerts
|

Effect of levothyroxine administration on intestinal P‐glycoprotein expression: Consequences for drug disposition*

Abstract: Expression of intestinal P-glycoprotein in humans appears to be influenced by thyroid hormones. The functional consequences need to be addressed in patients with hyperthyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 26 publications
5
58
0
Order By: Relevance
“…It has also been reported that the expression of P-gp is induced in duodenum of LTX-treated volunteers. 9) These results may re‰ect the fact that the duodenum is the initial site of exposure after the p.o. administration of LTX, although CYP3A2 mRNA expression was not diŠerent among the tissues.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…It has also been reported that the expression of P-gp is induced in duodenum of LTX-treated volunteers. 9) These results may re‰ect the fact that the duodenum is the initial site of exposure after the p.o. administration of LTX, although CYP3A2 mRNA expression was not diŠerent among the tissues.…”
Section: Discussionmentioning
confidence: 85%
“…Siegmund et al 9) reported that, although the expression of P-gp in duodenum was increased 3.8-fold by LTX treatment, the change in P-gp expression was associated with only minor alterations in the half-life of talinolol after both oral and intravenous administration. However, in our case, the increase of about 2-fold in the duodenal expression of P-gp induced by LTX greatly decreased the bioavailability of CyA to about a quarter of that in the control rats ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study (Siegmund et al, 2002), P-glycoprotein levels were increased in duodenal biopsy specimens from healthy human volunteers after administration of levothyroxine (L-T 4 ). However, the increase in ABCB1 mRNA levels was not statistically significant.…”
mentioning
confidence: 99%
“…Siegmund et al reported that P-gp mRNA expression and immunoreactive P-gp in the duodenums of healthy volunteers were increased after administration of levothyroxine. 19) Although obtained from human colorectal cancer, the Caco-2 cell line is capable of morphological and biochemical differentiation in vitro to form intestinal epithelia under normal culture conditions. 20) Transcript levels of ABC transporters except for breast cancer-related protein (BCRP) show a good correlation between jejunum and Caco-2 cells.…”
mentioning
confidence: 99%